1991
DOI: 10.1001/jama.1991.03470190072032
|View full text |Cite
|
Sign up to set email alerts
|

The Susceptibility of Young Adult Americans to Vaccine-Preventable Infections

Abstract: Patients.\p=m-\The study included 1547 US Army recruits who were inducted during September and October 1989. Outcome Measures.\p=m-\Seronegativityby various demographic factors. Results.\p=m-\Seronegativity rates, directly adjusted to the 15to 24-year-old US population in 1980, were 20.7% for measles, 15.6% for mumps, 17.5% for rubella, and 6.9% for varicella. For measles, mumps, and rubella, susceptibility was less in females, blacks, and college-educated recruits, and varicella susceptibility was greater i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
9
0
1

Year Published

1993
1993
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(12 citation statements)
references
References 26 publications
2
9
0
1
Order By: Relevance
“…Both national 27 and military [28][29][30] seroprevalence studies showed higher rates of varicella susceptibility among black subjects, compared with white subjects, for all age groups studied. Although the reasons for these findings are not well understood, one possible explanation may be the difference in child care center use for black children, compared with white children.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Both national 27 and military [28][29][30] seroprevalence studies showed higher rates of varicella susceptibility among black subjects, compared with white subjects, for all age groups studied. Although the reasons for these findings are not well understood, one possible explanation may be the difference in child care center use for black children, compared with white children.…”
Section: Discussionmentioning
confidence: 81%
“…26 Racial disparities in varicella disease rates and susceptibility were described in several studies that examined disease rates before vaccine licensure. 13,14,[19][20][21][27][28][29][30] In military populations, there were significantly greater rates of varicella among black adults, compared with white adults, before vaccine licensure. [19][20][21] Similar findings were reported from an analysis of data for a managed care population 14 and from an analysis of Connecticut state hospital discharge data.…”
mentioning
confidence: 99%
“…Similarly, Kelley et al conducted a national serological survey of US Army recruits and found lower susceptibility to measles in women. 18 Hutchins et al reported that among persons born in the vaccine era, male sex was an independent predictor of measles susceptibility. 19 The higher seropositivity in women might be partly due to sex differences in the humoral antibody response to measles vaccine.…”
mentioning
confidence: 99%
“…14 However, using the latter method, a serosurvey of preschool children from the US in the early 1990s reported a similar proportion of seropositive subjects to that in our preschool-aged group, 15 whereas a more recent (1997) US study of preschoolers found seropositivity levels of ≥94%, 16 and a study of US army recruits aged 17 to 23 years found 97% seropositive to type 1, 99% to type 2 and 87% to type 3. 17 The correlation between cut-off antibody titre, test method and protective immunity is uncertain, but a method with less sensitivity and greater specif icity should provide a more conservative estimate of immunity than a highly sensitive, less specific method. Serosurveys cannot easily be compared between different laboratories, but are useful to identify differences in seroprevalence in different age groups and monitor changes, in the same population, if the method remains constant.…”
Section: Discussionmentioning
confidence: 99%